Factors Affecting White Pepper Production in Puncak Village, South Sinjai District, Sinjai Regency - Fadilah Nurdin; Nurhalyza Nurhalyza; Nilmalasari Nilmalasari; Asdar Asdar; Salsabila Salsabila; Anisa Fahira Asma (FAKULTAS PERTANIAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2026)
This study aims to analyze farmer characteristics and the factors affecting white pepper production in Puncak Village, South Sinjai District, Sinjai Regency. This research employed a quantitative approach using a survey method. A total of 30 farmers were selected using a saturated sampling technique. Data were collected through interviews, observations, and documentation, and analyzed using multiple linear regression. The results show that partially, seed quality (X1), land area (X2), and price (X3) have a significant effect on white pepper production with significance values < 0.05. Seed quality and price have a positive effect, while land area has a negative effect on production. Simultaneously, all variables significantly affect production. The coefficient of determination (R²) is 0.411, indicating that 41.1% of the variation in production is explained by the model, while the rest is influenced by other factors outside the study. In conclusion, Farmers are encouraged to use high-quality seeds and optimize land management to boost white pepper productivity, particularly on large-scale plots, to prevent a decline in production efficiency. The government and agricultural extension officers should provide guidance and training on efficient white pepper cultivation techniques and proper land management to increase farmers’ yields.